The Role of Advanced Glycation End Products in Aging and Metabolic Diseases: Bridging Association and Causality - Chaudhuri, Jyotiska; Bains, Yasmin; Guha, Sanjib; Kahn, Arnold; Hall, David; Bose, Neelanjan; Gugliucci, Alejandro; Kapahi, Pankaj (Cell metabolism, 2018)
Accumulation of advanced glycation end products (AGEs) on nucleotides, lipids, and peptides/proteins are an inevitable component of the aging process in all eukaryotic organisms, including humans. To date, a substantial body of evidence shows that AGEs and their functionally compromised adducts are linked to and perhaps responsible for changes seen during aging and for the development of many age-related morbidities. However, much remains to be learned about the biology of AGE formation, causal nature of these associations, and whether new interventions might be developed that will prevent or reduce the negative impact of AGEs-related damage. To facilitate achieving these latter ends, we show how invertebrate models, notably Drosophila melanogaster and Caenorhabditis elegans, can be used to explore AGE-related pathways in depth and to identify and assess drugs that will mitigate against the detrimental effects of AGE-adduct development.